2020
DOI: 10.1177/1756286420951087
|View full text |Cite
|
Sign up to set email alerts
|

HDMTX-based polychemotherapy including intraventricular therapy in elderly patients with primary CNS lymphoma: a single center series

Abstract: Background: To investigate outcome and toxicity of high-dose systemic methotrexate (HDMTX)-based polychemotherapy and intracerebroventricular (ICV) chemotherapy via an Ommaya reservoir in elderly patients with primary central nervous system lymphoma (PCNSL). Methods: We performed a retrospective analysis on patients ⩾65 years with first diagnosis of PCNSL admitted to our center between January 2015 and December 2019. These patients were treated with a standardized chemotherapy protocol in case of absent contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Data regarding surgical treatment of PCNSLs is scarce. Previously published data agree that resection is discouraged [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 98%
“…Data regarding surgical treatment of PCNSLs is scarce. Previously published data agree that resection is discouraged [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 98%
“…In a retrospective study, Seigel et al reported a 60.5% CR rate and a median PFS of 16 months (8–24 months) in 46 patients ≥ 65 years treated with HD-MTX/ifosfamide/AraC as systemic therapy associated with IT injection of MTX with prednisolone and AraC. Toxicity was manageable [55 ▪ ]. Another retrospective study including 19 patients > 80 years, showed the feasibility of HD-MTX polychemotherapy in this population, with a median OS of 16.3 months [56].…”
Section: How To Treat Newly-diagnosed Elderly Patients With Primary C...mentioning
confidence: 99%
“…However, particularly in the elderly population, the risk-benefit balance is not clearly established between a potential improvement of PCNSL response versus the risk of an increase of immunosuppression. The phase 3, HOVON trial explored the M ethotrexate, BCNU, etoposide, Prednisone (MBVP) protocol with (n ¼ 99) or without rituximab (n ¼ 100), median age was 61 (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67). We only observed a trend in favor of rituximab, PFS at 1 years was 58% and 65% (P ¼ 0.18) and median OS was 56.7 months and not reached (P ¼ 0Á74) for R-MBVP and MBVP respectively [53].…”
Section: Rituximabmentioning
confidence: 99%
“…HD-MTX penetrates the meninges well and the use of intrathecal treatment (MTX and cytarabine) in patients with lymphomatous meningitis treated with HD-MTX has not been established in the absence of controlled trials. If used, these drugs are likely delivered through an intraventricular Ommaya reservoir with a reservoir infection rate of 9% [ 68 ]. This approach was proposed in some chemotherapy regimens, including those used with elderly patients [ 9 , 68 , 69 , 70 ], and may be discussed when intravenous MTX is administered at doses below 3 g/m 2 , to allow reaching cytotoxic levels in the CSF.…”
Section: Treatmentmentioning
confidence: 99%
“…If used, these drugs are likely delivered through an intraventricular Ommaya reservoir with a reservoir infection rate of 9% [ 68 ]. This approach was proposed in some chemotherapy regimens, including those used with elderly patients [ 9 , 68 , 69 , 70 ], and may be discussed when intravenous MTX is administered at doses below 3 g/m 2 , to allow reaching cytotoxic levels in the CSF.…”
Section: Treatmentmentioning
confidence: 99%